Filtering of neural signals by focused attention in the monkey prefrontal cortex. - Everling, S; Tinsley, C; Gaffan, D; Duncan, J (2002)
Prefrontal cortex is thought to be important in attention and awareness. Here we recorded the activity of prefrontal neurons in monkeys carrying out a focused attention task. Having directed attention to one location, monkeys monitored a stream of visual objects, awaiting a predefined target. Although neurons rarely discriminated between one non-target and another, they commonly discriminated between targets and non-targets. From the onset of the visual response, this target/non-target discrimination was effectively eliminated when the same objects appeared at an unattended location in the opposite visual hemifield. The results show that, in prefrontal cortex, filtering of ignored locations is strong, early and spatially global. Such filtering may be important in blindness to unattended signals--a conspicuous aspect of human selective attention.